Deep and dark and dangerous - Hahn, Mary Downing (New York : Clarion Books, 2007)
When thirteen-year-old Ali spends the summer with her aunt and cousin at the family's vacation home, she stumbles upon a secret that her mother and aunt have been hiding for over thirty years.
Keywords: Secrets; Ghosts; Mothers and daughters; Cousins